2019
DOI: 10.3389/fphar.2019.00038
|View full text |Cite
|
Sign up to set email alerts
|

Dual Tumor Suppressor and Tumor Promoter Action of Sirtuins in Determining Malignant Phenotype

Abstract: Sirtuins (SIRTs), class III histone deacetylases, are differentially expressed in several human cancers, where they display both oncogenic and tumor-suppressive properties depending on cellular context and experimental conditions. SIRTs are involved in many important biological processes and play a critical role in cancer initiation, promotion, and progression. A growing body of evidence indicates the involvement of SIRTs in regulating three important tumor processes: epithelial-to-mesenchymal transition (EMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 170 publications
(199 reference statements)
4
104
0
Order By: Relevance
“…Sirtuins have been implicated in different cellular processes, being key epigenetic modulators of EMT activation and maintenance [23,24]. Interestingly, SIRT1 has been shown to play a dual role in tumorigenesis, acting either as an oncogene or tumor suppressor gene according to the tumor context [23,27].…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuins have been implicated in different cellular processes, being key epigenetic modulators of EMT activation and maintenance [23,24]. Interestingly, SIRT1 has been shown to play a dual role in tumorigenesis, acting either as an oncogene or tumor suppressor gene according to the tumor context [23,27].…”
Section: Discussionmentioning
confidence: 99%
“…The sirtuins (SIRTs), are a family of highly-conserved histone deacetylases (HDACs) that are differentially expressed in several human cancers, where they display both oncogenic and tumor-suppressive properties depending on cellular context and experimental conditions [97]. SIRTs have also been shown to regulate a wide variety of cellular processes beyond transcriptional repression in varied subcellular compartments and in different cell types [97]. SIRT6 is unique in its constitutive localization to chromatin [98] and has been shown to regulate many important pathways via epigenetic mechanisms, mainly histone deacetylation.…”
Section: Sirt1 Sirt6 and Metabolism Regulationmentioning
confidence: 99%
“…Recent overviews of the literature revealed that SIRT4, although first described as a metabolic tumor suppressor 37 , may display both tumor suppressor and oncogenic/cancer promoting activities, depending on the tumor type and checkpoint activating conditions 72,73 . Our data on the putative SIRT4-HDAC6-microtubule dynamics axis are rather consistent with an extramitochondrial tumor suppressor function of SIRT4.…”
Section: Discussionmentioning
confidence: 99%